2021
DOI: 10.18632/oncotarget.27857
|View full text |Cite
|
Sign up to set email alerts
|

Total lesion glycolysis in oral squamous cell carcinoma as a biomarker derived from pre-operative FDG PET/CT outperforms established prognostic factors in a newly developed multivariate prediction model

Abstract: Purpose: Retrospective study to investigate the impact of image derived biomarkers from [ 18 F]FDG PET/CT prior to surgical resection in patients with initial diagnosis of oral squamous cell carcinoma (OSCC), namely SUV max , SUV mean , metabolic tumor volume (MTV) and total lesion glycolysis (TLG) of the primary tumor to predict overall survival (OS). Materials and Methods: 127 subsequent patients with biopsy-proven OSCC were included who underwent [ 18 F]FDG PET/CT before surgery. SUV max , SUV mean , MTV an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
2
2
0
Order By: Relevance
“…In line with previous studies demonstrating a correlation between metabolic activity, survival and clinicopathological features in OSCC [ 48 , 49 , 51 , 52 ], we were able to confirm these findings in the present study. Analysis of SUVmax values among patients with OSCC—divided into two groups according to a statistically calculated cut-off value—showed highly significant differences in survival, with higher survival rates in the low SUVmax group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous studies demonstrating a correlation between metabolic activity, survival and clinicopathological features in OSCC [ 48 , 49 , 51 , 52 ], we were able to confirm these findings in the present study. Analysis of SUVmax values among patients with OSCC—divided into two groups according to a statistically calculated cut-off value—showed highly significant differences in survival, with higher survival rates in the low SUVmax group.…”
Section: Discussionsupporting
confidence: 93%
“…Berghmans et al also highlighted this connection early in their review of the predictive value of SUVmax on survival times in patients with non-small-cell lung cancer (NSCLC) and identified a survival-dependent threshold for SUVmax [ 44 ]. In further studies on OSCC, the same correlations were observed [ 36 , 48 , 49 , 50 , 51 ]. Based on these pre-existing studies, we evaluated a potential survival-dependent impact of SUVmax for OSCC patients and established a tumor-specific threshold by use of ROC analyses.…”
Section: Discussionsupporting
confidence: 67%
“…While MV 4 , 9 14 , 21 , 22 and TLG (SUV) have been extensively studied in the context of oncological disorders, our current study is one of the few that investigates the diagnostic performance of these 18 F-FDG PET/CT-derived PET parameters (or their SUR-based variant) in the context of IE. In that regard, Avramovic et al have previously compared the diagnostic value of MV with SUVmax in patients with left ventricular assist devices (LVADs).…”
Section: Discussionmentioning
confidence: 99%
“…OSCC staging, including the TN-stage, and surgical margin status are the most established clinical prognostic factors ( 19 ). Imaging-based biomarkers, including CT, magnetic resonance imaging, and F-fluorodeoxyglucose positron emission tomography/CT parameters, are established prognostic factors for OSCC ( 20 , 21 ). Recently, molecular biomarkers quantified through liquid and tissue biopsy have been reported ( 2 , 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%